Effekte einer pflanzlichen Crataegus-Campher-Kombination auf die Symptomatik funktioneller Herz-Kreislauf-Störungen - Schmidt, Ulrich; Albrecht, Martina; Schmidt, Stefan (Arzneimittelforschung, 2000)
Effects of a Herbal Crataegus-Camphor Combination on the Symptoms of Functional Cardiovascular DisordersOne hundred and ninety (190) patients presenting with “functional cardiovascular disorders” (ICD 10, F 45.3) received purely herbal combination therapy comprising crataegus and camphor (Korodin® Herz-Kreislauf-Tropfen) or a placebo, identical in colour and taste to the active treatment, over a period of four weeks within the scope of a multi-centre, placebocontrolled, double-blind study.The principal criterion was the fall in the overall score obtained for a heart-related symptom complex (HSK) during administration of the herbal combination or randomly allocated placebo. The overall score fell significantly by 5.5 or 4.5 points, respectively, from a baseline value of 10.0 points each (p = 0.0165). The sub-score for exhaustion, joint pain, heart disorders, pain on pressure and the total score on the Giessen discomfort chart (GBB) indicated better efficacy with the crataegus-camphor combination than with the placebo. On completion of treatment, the investigators assessed the efficacy of the active drug as „very good to good” in 70.5% of their patients compared with a similar evaluation in just 49.5% of the placebo patients.The degree of satisfaction with the drug therapy according to physician and patient reflected the objective results obtained. 71.6% of subjects in the active drug group were satisfied with their treatment compared with just 52.7% in the placebo group.Adverse events (undesirable side effects) were recorded in 8.3% and 8.5% of patients, respectively. A correlation with the active drug therapy was established in only two cases. Tolerance was therefore positively assessed.
Keywords: Camphor; Cardiovascular disorders, functional; Crataegus; Korodin®, clinical studies, effects on functional cardiovascular disorders